2016
DOI: 10.1002/nbm.3604
|View full text |Cite
|
Sign up to set email alerts
|

An illustrated comparison of processing methods for phase MRI and QSM: removal of background field contributions from sources outside the region of interest

Abstract: The elimination of so-called background fields is an essential step in phase MRI and quantitative susceptibility mapping (QSM). Background fields, which are caused by sources outside the region of interest (ROI), are often one to two orders of magnitude stronger than tissue-related field variations from within the ROI, hampering quantitative interpretation of field maps. This paper reviews the current literature on background elimination algorithms for QSM and provides insights into similarities and difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
205
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(211 citation statements)
references
References 43 publications
6
205
0
Order By: Relevance
“…More accurate BFR could potentially overcome this problem. Here, however, we used 2 state‐of‐the‐art techniques with similar results, and it has been shown that all known BFR techniques lead to errors toward the mask edges . The error introduced by the SC step is probably because of regions of the local field map being cut off at reduced coverage (Figure B, red arrows).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More accurate BFR could potentially overcome this problem. Here, however, we used 2 state‐of‐the‐art techniques with similar results, and it has been shown that all known BFR techniques lead to errors toward the mask edges . The error introduced by the SC step is probably because of regions of the local field map being cut off at reduced coverage (Figure B, red arrows).…”
Section: Discussionmentioning
confidence: 99%
“…This was repeated with the above QSM pipeline but with LBV as the background field removal (BFR) step to examine how the results are affected by different BFR techniques. LBV was chosen because it was shown to perform similarly well to PDF in the brain while introducing slightly different error patterns near the tissue edges …”
Section: Methodsmentioning
confidence: 99%
“…A mask delineating the region of the local effects of interest has to be defined. Many background-correction methods presented in literature will either end up eroding this mask (losing relevant information on outer parts of the brain) or giving values that are unreliable close to the boundary, for an illustrated comparison of many of these methods refer to (Schweser et al, 2016). The second step is the calculation of the QSM from the measured field maps (after background field removal).…”
Section: Introductionmentioning
confidence: 99%
“…This is commonly referred as the “shadowing” artifact. Past studies have shown that background‐removal (and single‐step) algorithms can effectively eliminate large‐scale (externally sourced) fields that are severely truncated by information loss due to low SNR or FOV definition, hence simplifying the problem into inverting local dipole fields that are only partially truncated by ROI masking. However, due to these and other confounding factors (e.g., nonzero transmit‐driven initial phases, unwrapping errors), the efficiency of background‐removal algorithms is often impaired leading to excessive local‐field contamination (Figure ).…”
Section: Discussionmentioning
confidence: 99%